A physically-based failure analysis framework for fiber-reinforced composite laminates under multiaxial loading. (1st June 2020) - Deng, Jian; Hong, Zhenjun; Yin, Qiaozhi; Lu, Tian Jian
Abstract: Fiber reinforced composites are widely accepted as efficient alternatives for designing light-weight and high-performance structures, yet theoretical prediction of failure for such composites is still a challenging task with uncertainties and controversies. In this work, a new physically-based failure analysis framework is proposed to predict both intralaminar failure onset and strengths for composite laminates under general stress states, with interactive and coupling effects of stresses fully considered. The in situ strengths are introduced using the simplified fracture mechanics-based approximation formula where the constraining effects of both the adjacent plies and embedded laminar thickness are considered. The proposed framework is validated by comparing predictions with existing experimental data. Both initial and final failure envelopes are well predicted for unidirectional and multi-directional laminates under multiaxial loads. Stress-strain responses are also well captured, further illustrating the influence of in situ strengths on failure initiation.